Outcome of nutritional intervention measures at a nutrition rehabilitation centre in Krishna district, Andhra Pradesh - Pagali, Deepthi; Bollipo, Suneetha; Korrapolu, Harsha B.; Rahman, Mohammed Abdul (International Journal Of Community Medicine And Public Health, 2018)
Background: Nutrition rehabilitation centre (NRC) is a unit in a district health facility, where children with severe acute malnutrition are admitted and provided with nutritional and therapeutic care. Methods: Analysis of nutritional data of all the children admitted to NRC at Krishna district from January 2017 to July 2018. Statistical analysis was done using SPSS. Results: A total of 200 children were included in the study. The overall mean weight at admission was found to be 8.30 kg with a standard deviation of 2.35 kg and the mean weight at the time of discharge is 9.57 kg with a standard deviation of 2.61 kg. There is a statistically significant difference in weight and mid arm circumference at admission and discharge. Mean duration of hospital stay is around 18.67±5.4 days. Target weight is achieved in 71% of the study group. Conclusions: Present study reflects that NRCs have been playing a key role to cope up with the problem of severe acute malnutrition as demonstrated by a high rate of weight gain at discharge as well as during follow ups.